Pyrrhonian scepticism and Hegel's theory of judgement : a treatise on the possibility of scientific inquiry - Trisokkas, Ioannis. (Critical Studies in German Idealism, 2012)
Hegel's Science of Logic is widely acknowledged as one of the greatest works of European philosophy. However, its contribution to arguably the most important philosophical problem, Pyrrhonian scepticism, has never been examined in any detail. Pyrrhonian Scepticism and Hegel's Theory of Judgement fills a great lacuna in Hegel scholarship by convincingly proving that the dialectic of the judgement in Hegel's Science of Logic successfully refutes this kind of scepticism. Although Ioannis Trisokkas has written the book primarily for those students of philosophy who already have an interest in Hegel's epistemology and philosophy of language and/or his Science of Logic , it will also appeal to those who investigate the problem of scepticism independently of the Hegel corpus.